Factors Affecting the Efficiency of Procurement Management in Educational Institutions under the Office of Vocational Education Commission in Phichit Province - Sooksa-ard, Itthipol; Rukponmongkol, Poompipat (Journal of Graduate MCU KhonKaen Campus, 2025)
The purposes of this thesis were 1. investigate the factors affecting the inventory management of educational institutions under the Phichit Vocational Education Office, which is affiliated with the Office of the Vocational Education Commission; 2.examine the efficiency of inventory management in educational institutions under the Phichit Vocational Education Office; 3. identify the relationships that influence the efficiency of inventory management in these institutions; and 4. develop a predictive equation for inventory management efficiency using the factors influencing inventory management as predictors. The sample used in this study included 175 administrators, teachers, and staff from educational institutions under the Phichit Vocational Education Office. The data collection tool was a 5-point Likert scale questionnaire. The statistical methods used for data analysis included mean, standard deviation, correlation analysis, normal regression analysis, and stepwise multiple regression analysis. The results of the study were as follows: 1. The overall factors affecting the inventory management of educational institutions under the Phichit Vocational Education Office were found to be at the highest level. 2. The overall level of the factors affecting inventory management in these institutions was high. 3. The factors affecting inventory management that were most strongly related to the efficiency of inventory management in these institutions were budget factors, while the least related factor was demand determination. 4. Using normal multiple regression analysis (Enter Multiple Regression Analysis), it was found that all three variables were significant predictors of inventory management efficiency in educational institutions under the Phichit Vocational Education Office. Planning, demand determination,and organizational management factors had a predictive power of 26.40%. Using (Stepwise Multiple Regression Analysis) to predict in raw scores and standard scores the results were as follows Prediction equation in raw scores: Y = 2.761 + .187 (X2) + .150 (X4) + .068 (X5) Prediction equation in standard scores: Z = .328 (X2) + .234 (X2) + .136 (X2)